Antibiotic Effect of Polyphenolic Compound Extracted from Tamarind (Tamarindus indica L.) Seed Coat on Productive Performance of Broilers - Aengwanich, W.; Suttajit, M.; Srikhun, T.; Boonsorn, T. (International Journal of Poultry Science, 2009)
An experiment was conducted to evaluate the effect of tamarind seed coat extract on the average daily weight gain, feed intake and feed conversion rate of broilers. Broilers were divided into 6 groups and received polyphenols from tamarind seed extract at 0 (control), 100, 200, 300, 400 and 500 mg/kg in their diets for 21 days. The results revealed the following information: During the period of 36-42 days of age, the average daily weight gain of broilers that received tamarind seed coat extract at 100 mg/kg in their diet was significantly higher than the weight gain of broilers that received tamarind seed coat extract at 0, 200, 400 and 500 mg/kg in their diets (p<0.05). Throughout the experimental period, the average daily weight gain tended to be highest in the group that received tamarind seed coat extract at 100 mg/kg in their diet. The feed intake and feed conversion rate of broilers in all groups were not significantly different (p>0.05). This study demonstrated that tamarind seed coat extract has a property similar to antibiotic feed additives and provides slightly improved average daily weight gain.